The Italian economy - Zamagni, Vera, 1943- (World economies., 2018)
The legacies of two great civilizations-the Roman Empire and Renaissance city-states--are still apparent in today's Italian economy in its internationalization, strong regional cultures, tourism, and arts industries. Less appreciated is the country's status as continental Europe's second-largest industrial power, notwithstanding the disproportionate significance of SMEs in Italy. Vera Zamagni's survey of the Italian economy and its modern history outlines its unique shape and structure and how human factors explain its strengths in social networks, "niche capitalism," and well-being indicators, as well as its weaknesses reflected in regional imbalances, political instability, and recently in banking. --